Determinants of Low Exclusive Breastfeeding Coverage in Indonesia - Nirna Dwi Anggraini; Ghaisani Putri Budhiharto; Azzahra Putri Nurkholis; Rouzatul Fitri; Chahya Kharin Herbawani (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Exclusive breastfeeding (EBF) coverage in Indonesia has not yet reached the national target of 80%, despite a gradual increase from 73.79% in 2023 to 74.73% in 2024. Several determinants contribute to this condition, including maternal employment, educational level, socio-cultural beliefs, and delayed early initiation of breastfeeding (IMD). Suboptimal EBF practices increase the risk of stunting, hinder optimal growth and development, and reduce overall child health outcomes. Objective: This study aims to identify key factors associated with low EBF coverage in Indonesia and to formulate evidence-based strategies for improvement by considering demographic, socio-economic, cultural, and occupational challenges, particularly among working mothers. Methods: An integrative literature review was conducted by analyzing 11 peer-reviewed articles retrieved from the GARUDA, Springer, DOAJ, and ScienceDirect databases. Inclusion criteria were open-access articles published between 2021 and 2025 using quantitative or qualitative research designs. Thematic analysis was applied to synthesize determinants influencing EBF coverage. Results: The review identified maternal education, employment status, family support, IMD implementation, place of delivery, and access to breastfeeding counseling as major determinants of EBF practices. Conclusion: EBF coverage in Indonesia is shaped by multifactorial influences, highlighting the need for integrated educational, familial, and policy-based interventions.